PERENCANAAN PENGELOLAAN SAMPAH DOMESTIK DI NAGARI LUBUK BUNTA KECAMATAN SILAUT KABUPATEN PESISIR SELATAN, PROVINSI SUMATERA BARAT - Nadya Rahayu Valdira; Khalila Khairani; Taufiq Ihsan (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
Garbage is a problem that exists in every region in Indonesia, one of which is in Nagari Lubuk Bunta, Silaut District, Pesisir Selatan Regency. Nagari Lubuk Bunta includes inaccurate waste management because the residents of Nagari Lubuk Bunta only burn their waste; this will undoubtedly cause air pollution. The concrete waste services provided by the Environmental Service of Pesisir Selatan Regency for Nagari Lubuk Bunta do not exist. Increasing the population will increase the waste generation in the village. Nagari Lubuk Bunta is one of the nagari in Pesisir Selatan Regency, a total waste generation of 3.11 m3 / day in 2019. This activity is quantitative and qualitative, which forms the basis for proposing waste management in Nagari Lubuk Bunta. Quantitative data were obtained from generation studies and literature. This activity results in urban-scale waste management, starting from a container, collection, transportation, processing, and final disposal.